Pembelaan Terpaksa sebagai Alasan Pembenar dalam Rangka Pembelaan Diri - Chatarina Dwi Agista; Ade Adhari (Syntax Literate, 2023)
Reasons for abolishing punishment are reasons that allow people who commit criminal acts not to be sentenced to punishment. There are two categories of reasons for criminal abolition, namely, excuses and justification reasons. Noodweer is contained in Article 49 Paragraph (1) of the Criminal Code is part of the justification. In this research, it will be explained about the application of justification reasons as reasons for abolishing crimes in the context of self-defense against perpetrators of murder. The research is based on a descriptive method using a qualitative type of approach, and is carried out using a literature review method. Basically, the actions of a person categorized as an act of defense must fulfill the specified conditions, namely: there must be an attack or threat of attack, is unlawful, the attack is aimed at oneself, honor, decency or one's own or other people's property, and is forced to do so. In order to fulfill the intended elements, there are 2 (two) important conditions, namely the fulfillment of the requirements of proportionality (balance) and carried out in the lightest way. However, in practice there are still many law enforcement officers who are not brave enough to decide on someone who has committed a crime using the excuse of a criminal offense